Actinic patterned mask imaging using extreme ultraviolet ptychography microscope with high harmonic generation source. (1st July 2022) - Kim, Young Woong; Lee, Dong Gi; Moon, Seungchan; Ku, Chang Mo; Cho, Joong Hwee; Ahn, Jinho
Abstract: Extreme ultraviolet (EUV) lithography is expected to be used for 3 nm technology nodes and beyond, yet the need for actinic mask metrology and inspection remains a critical challenge. In this study, we demonstrate an EUV ptychography microscope as a high-harmonic generation-based actinic mask imaging tool. A series of diffraction patterns on an EUV mask is used to reconstruct both the amplitude and phase information of the periodic patterns using ptychographic algorithms. The results show that the EUV ptychography microscope has the potential for determining the actinic metrology of EUV masks and providing phase information for EUV mask development.